'You're the best liar in the world': a grounded theory study of rowing athletes' experience of low back pain. Issue 6 (9th October 2020) - Wilson, Fiona; Ng, Leo; O'Sullivan, Kieran; Caneiro, J P; O'Sullivan, Peter PB; Horgan, Alex; Thornton, Jane S; Wilkie, Kellie; Timonen, Virpi
Abstract : Objectives: Low back pain (LBP) is common in rowers and leads to considerable disability and even retirement. The athlete voice can help clinicians to better understand sport-related pain disorders. We aimed to capture the lived experience of LBP in rowers. Methods: Cross-sectional qualitative study using a grounded theory approach. Adult competitive rowers with a rowing-related LBP history were recruited in Australia and Ireland. Data were collected through interviews that explored: context around the time of onset of their LBP and their subsequent journey, experiences of management/treatment, perspectives around present beliefs, fears, barriers and expectations for the future. Results: The 25 rowers (12 women/13 men) who participated were aged 18–50 years; they had a mean 12.1 years of rowing experience. They discussed a culture of concealment of pain from coaches and teammates, and fear of being judged as 'weak' because of the limitations caused by LBP. They reported fear and isolation as a result of their pain. They felt that the culture within rowing supported this. They reported inconsistent messages regarding management from medical staff. Some rowers reported being in a system where openness was encouraged—they regarded this a leading to better outcomes and influencing their LBP experience. Conclusions: Rowers' lived experience of LBP was influenced by a pervasive culture of secrecy around symptoms. Rowers and support staff should be educated regarding the benefits of early disclosure and rowers should be supported to do so without judgement.